Waste rocks and medieval slag as sources of environmental pollution in the area of the Pb-Zn Mine Rudnik (Serbia) - Zdravković, Alena; Cvetković, Vladica; Šarić, Kristina; Pačevski, Aleksandar; Rosić, Aleksandra; Erić, Suzana (Journal of geochemical exploration, 2020)
The new geochemical and mineralogical data of soil and water from the PbZn Rudnik Mine area (central Serbia) reveal that the areas close to the mining sites and those located remotely from them are both affected by significant pollution by toxic elements, especially As, Pb, Ni and Cr. We, therefore, propose that two main sources are generally responsible for the current state of pollution in this area. The first is the material from waste rock dumps (WRDs) in which the decomposition of primary sulfides plays the most important role. Our results also demonstrate that both sulfides that serve as main carriers of toxic elements, such as galena (Pb) and arsenopyrite (As), and those that carry toxic elements in microquantities act as pollution factors. This pollution affects soil and water in the immediate surroundings of the WRDs, and it is likely combined with the influence of waste mining waters and from rocks from the geological basement. The second source is medieval slag that is related to the pollution of soil and water located at higher altitudes and far away from WRDs. The results of our study argue that leaching of toxic elements is caused by the slag weathering and that this environmental impact can only partly be suppressed by the formation of hardly soluble secondary phases, such as linarite, brochantite and beaverite. Although the presented pollution models are schematic and cannot account for the entire environmental complexity of the Rudnik Mine site, they do represent a solid basis for further environmental studies in this area. [Display omitted] •The pollution as the result of two sources in the area of PbZn mine•Pollution caused by sulfide decomposition in material from waste rock dumps•The environmental pollution caused by decomposition of medieval slag